Analisis Deskriptif Current Ratio, Debt to Asset Ratio dan Return on Asset pada PT Tempo Scan Pasific Tbk - Nabillaa, Nabillaa; Puji Muniarty (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to determine the condition and development of the Current Ratio (CR), Debt to Asset Ratio (DAR), and Return on Assets (ROA) at PT Tempo Scan Pacific Tbk during the period 2016–2025. The research method used is a quantitative descriptive method using secondary data in the form of the company's annual financial reports. Data collection techniques were carried out through documentation and literature studies. Data analysis was carried out by calculating financial ratios using the Current Ratio, Debt to Asset Ratio, and Return on Asset formulas, then analyzed descriptively through tables and interpretation of the company's financial ratio developments. The results of the study indicate that the company's Current Ratio is in very good and stable condition because it is always above the general liquidity standard. The Debt to Asset Ratio shows a downward trend in recent years, thus reflecting the company's healthy solvency condition with a relatively low debt level. Meanwhile, Return on Assets shows quite good development despite experiencing a decline in 2017–2018. The company was able to maintain a stable level of profitability until the end of the study period. Overall, the company's financial condition is considered healthy, stable, and able to manage assets and liabilities efficiently.